The Integration of Community Problem Analysis and Involvement in Teaching and Learning - Thaochalee, Kanjana; Puington, Pongpun; Chanruechai, Kitisak; khamhom, Chalita (International Journal of Membrane Science and Technology, 2023)
As a participatory action research approach, the participatory problem-solving learning process incorporates teaching and learning by applying active learning methodologies and instruments to analyze community problems. The target group comprised 40 people, split into 10 undergraduate students and 30 community leaders, based on quantitative and qualitative data. Active learning methods used in research on learning growth involve students in developmental learning activities. Integrating teaching and learning activities into a suitable community and social development in a tangible manner through a process of practice outside the classroom through community engagement. Participants and researchers collaborate to design teacher-student interactions that emphasize student action and participatory assessment. Students and teachers can collaborate to create a work division planning process, which includes the following steps: work planning, tool study, job description division, operational calendar, coordination, community context study, implementation process, improvement, problem solving, and development of tools to analyze community problems. Research has found that learners learn and develop skills through self-practice, such as going to an area and finding community problems. This was a problem-solving skill practice from real situations in the community, and self-assessment and community assessment in enabling students to discover their own flaws and lead to self-development.